Effectiveness of delivering evidence-based eating disorder treatment via telemedicine for children, adolescents, and youth. Issue 1 (2nd January 2023) - Steinberg, Dori; Perry, Taylor; Freestone, David; Bohon, Cara; Baker, Jessica H.; Parks, Erin
ABSTRACT: Barriers limit access to eating disorder treatment. Evidence-based treatment delivered using telemedicine could expand access. This study determined the effectiveness of enhanced Family-Based Treatment (FBT+) delivered using telemedicine for children and adolescents with eating disorders. Participants had a confirmed eating disorder diagnosis, lived in states where treatment was available, and lived with a family member willing to participate. Virtual FBT+ was administered by a five-person team including a therapist, dietitian, medical provider, peer mentor, and family mentor for up to 12 months. Measures were recorded at baseline and varying frequencies throughout treatment. Weight was self-reported. Eating disorder symptoms were assessed with the Eating Disorder Examination-Questionnaire Short Form (EDE-QS) and depression and anxiety were measured using the Patient Health Questionnaire-9 (PHQ-9) and General Anxiety Disorder-7 (GAD-7). Caregiver burden and self-efficacy were measured using the Burden Assessment Scale, and Parent Versus Eating Disorder scale. The majority of patients (N = 210; 6 to 24 years old [mean 16 · 1 years]) were cisgender female (83%) White, (71%), required weight restoration (78%), and had anorexia nervosa, restricting type (63%). After 16 weeks, patients on weight restoration gained on average 11 · 3 [9 · 86, 12 · 8] pounds and the average change in EDE-QS score was −6 · 31 [−8 · 67, −4 · 10] points. Similar reductions were seen for depression (−2 · 62 [−4 · 24, −1 · 04]), anxiety (−1 · 44 [−1 · 12, 0 · 78]), and caregiver burden (−4 · 41 [2 · 45, 6 · 31]). Caregiver self-efficacy increased by 4 · 56 [3 · 53, 5 · 61] points. Patients and caregivers reported satisfaction with treatment. Virtual FBT+ for eating disorders can transcend geographical and psychosocial treatment barriers, expanding access to evidence-based eating disorder treatment.